PENGABAIAN MAKSIM OLEH TOKOH UTAMA FILM CARS 2 - ARIPTA, GILANG (Jurnal Ilmiah Mahasiswa FIB, 2013)
The writer conducts a study about flouting maxim in ‘Cars 2’ film. There are two problems of the study to be solved, namely: (1) What maxims are flouted by the main characters of the film Cars 2? (2) What is the implied meaning of the flouted maxim from the main characters’ utterances of the film Cars 2? This study uses qualitative approach. While content analysis is used to analyze the conversation between the main characters in ‘Cars 2’ film. This study reveals that only three of four maxims from the cooperative principle are flouted in the film, which are: maxim of quantity, maxim of quality, and maxim of relation. Maxim of quality is mostly flouted by the main characters of the film. The writer suggests the next researchers explore more about cooperative principles such as by combining the cooperative principle with another pragmatics field of study, such as politeness strategies, to reveal the possible relation between these two different principles. Kata kunci: pengabaian maksim, prinsip kooperatif, ilmu pragmatik.